2020
DOI: 10.22460/project.v3i3.p337-347
|View full text |Cite
|
Sign up to set email alerts
|

Millennial Lecturers’ Attitudes in Incorporating the Online Application in the Efl Classroom

Abstract: Millennial lecturers are considered to be proficient in teaching by making use of the technology in their classrooms. Nine millennial lecturers were involved in this study. It was carried out as qualitative research. The data collection technique was open-ended questionnaires then analyzed through thematic analysis. Three research questions were aimed to be examined. The first one was the investigation on the variety of the online applications used in the EFL classrooms; the second one was questioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Some studies share similar findings to those conveyed in the excerpts above (Musliha & Purnawarman, 2020;Sari et al, 2020). As admitted by David, Mentimeter can be used to generate more interaction with students, so that learning does not focus on the teacher but on the students.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Some studies share similar findings to those conveyed in the excerpts above (Musliha & Purnawarman, 2020;Sari et al, 2020). As admitted by David, Mentimeter can be used to generate more interaction with students, so that learning does not focus on the teacher but on the students.…”
supporting
confidence: 59%
“…The intention of implementing an online application like Mentimeter at the beginning of the lesson is so that students pay attention, since technology is so relevant to millennials (Cahyani & Cahyono, 2012). Moreover, according to Sari et al (2020), the use of online apps like Mentimeter can create a positive mood in the class. So, by having an online app like Mentimeter, the teachers intend to give a good impression and use something that is relevant to the students in order to gain their participation.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The finding in this study was in the contrary with Sari at al did. It found that students were prefer to technological tools than the printed material for learning (Sari et al, 2020). The fact, in this pandemic situation, the informants agree that the online class utilization has the inactive class, rather than in face to face learning.…”
Section: Tabel 1 the Advantages And Disadvanatges Of Online Learningmentioning
confidence: 93%
“…Studies also found that most instructors reported greater confidence in their ability to teach remotely and to integrate and apply technology in teaching (Heldt et al , 2021; Lowther et al , 2008). In addition, positive attitudes were found toward integrating different types of smartphone applications in the teaching process (Sari et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The reforms presented instructors with complex challenges (DePietro, 2020). Instructors have been required to develop cognitive and social skills that underlie success in the remote learning environment (Scull et al, 2020) and technological skills that include the use of a variety of digital tools and applications (DePietro, 2020;Nasri et al, 2020). For many instructors, the transition to online teaching was not easy, as some were not skilled in the use of the required technology; therefore, digital gaps between them were observed (Hodges et al, 2020).…”
Section: Introductionmentioning
confidence: 99%